The effects of foreign direct investments and economic growth on employment and female employment: A time series analysis with structural breaks for Turkey - A. Oznur Umit; H. Isil Alkan (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this paper is to examine the effects of foreign direct investments and economic growth on employment and female employment in Turkey with quarterly data for 2000:Q1-2013:Q4 terms. Design/ Methodology/Approach - The data were obtained from Electronic Data Delivery System (EDDS) of the Central Bank of the Republic of Turkey (CBRT), Turkish Statistical Institute (TURKSTAT) and International Financial Statistics (IFS). The stationarity of variables are analysed with Carrion-i Silvestre et. al. (2009) unit root test with multiple structural breaks and the cointegration relationship between variables is tested with Maki (2012) cointegration test with multiple structural breaks. Dynamic ordinary least squares (DOLS) method is used for estimating cointegration coefficients. Findings - It is revealed with the study that foreign direct investments affect employment and female employment negatively whereas economic growth affect employment and female employment positively. Orginality/ value - Despite various studies exploring the relationship between FDI and employment, studies examining the relationship between FDI and female employment are absent in the literature. From this point of view, this study can be seen as the precursor for enlightening the gender dimension of the subject.
Keywords: C32; E24; F21; F40; 330; Employment; Female Employment; Foreign Direct Investment; Economic Growth; Unit Root and Cointegration Tests with Multiple Structural Breaks